Measurement of Ar resonance and metastable level number densities in argon containing plasmas. (10th August 2017) - Fiebrandt, Marcel; Hillebrand, Bastian; Spiekermeier, Stefan; Bibinov, Nikita; Böke, Marc; Awakowicz, Peter
Abstract: The resonance 1 s 4 ( 3 P 1 ), 1 s 2 ( 1 P 1 ) and metastable 1 s 5 ( 3 P 2 ), 1 s 3 ( 3 P 0 ) level number densities of argon are determined by means of the branching fraction method in an inductively coupled plasma at 5 Pa and 10 Pa in argon with admixture of hydrogen, nitrogen and oxygen. The 1 s 5 ( 3 P 2 ) densities are compared to laser absorption spectroscopy measurements to evaluate the reliability of the branching fraction method and its limitations. The results are in good agreement and the use of a compact, low cost, low resolution spectrometer ( Δ λ = 1.3 nm) is sufficient to reliably determine the first four excited states of argon in argon-hydrogen and argon-oxygen mixtures. The addition of nitrogen results in unreliable densities, as the observed argon lines overlap with emission of the N 2 ( B 3 Π g − A 3 Σ u + ) transition.